Effect of Family-Based Education on Improving Family Health Tasks in Preventing the Transmission of Covid-19 - Lia Meilianingsih; Citra Windani Mambang Sari (IJNP (Indonesian Journal of Nursing Practices), 2023)
Background: During the 2020 pandemic, West Java established 4 red zones (where the transmission of Covid-19 was considered high), one of the cities was Cimahi. Based on the data, the accumulation cases was dominated by family clusters, so the government established policies to protect family members from Covid-19 transmission, namely modifying behaviours relating to carrying out activities by implementing health protocols. Consistency in implementing health protocols is way to prevent the transmission of Covid-19. Family-based education also has an important role to socialize and teach family members about health protocols that must be adhered to during the Covid-19 pandemic. The existence of Family-based has been found to improve the implementation of health tasks in the family.Objective: This study aims to determine the effect of family-based education on improving family health tasks in preventing the transmission of Covid-19.Methods: The research design used a quasi-experimental pre- and post-test control group design. The research respondents were 31 families for the intervention group and 31 families for the control group. The sampling technique was proportional random sampling. The educational intervention as provided in 3 meetings. Data analysis used Wilcoxon and Mann-Whitney.Results: The results showed that there family-based education had an effect  on increasing family health tasks relation to the prevention of the transmission of Covid-19 because the p-value was 0.000.Conclusions: Therefore, it was recommended that the head of the Public Health and Disease Control program implement family-based education in order to prevent the transmission of Covid 19 within the family and community.